2021
DOI: 10.14710/jil.19.3.638-648
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Kelimpahan Mikroplastik di Biota Perairan

Abstract: Sampah plastik dapat terdegradasi menjadi mikroplastik (MP) dan nanoplastik (NP) melalui proses fisik, kimia, dan biologis. MP didefinisikan sebagai partikel plastik kecil berukuran < 5 mm. MP saat ini telah ditemukan di tubuh biota perairan, baik perairan permukaan maupun perairan laut. Tujuan penelitian ini adalah mengkaji MP pada biota perairan. Metode yang digunakan dalam penelitian ini adalah studi literatur terhadap artikel publikasi 10 tahun terakhir. Kajian dilakukan terhadap kelimpahan, ukuran, ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
6
0
3
Order By: Relevance
“…The graph of the Abundance of microplastics in fish is presented in Figure 4. A study conducted by (Septiana et al, 2021) showed that microplastic content was also found in Channa striata species in Samarinda City (Sandra and Radityaningrum, 2021), showing the Abundance of microplastics in Oreochromis niloticus species in brackish waters of 1.47-7 particles/individual, and (Hasibuan et al, 2021) showed an abundance of microplastic 4.06-18.46 particles/individual in the Oreochromis mossambicus species. The main factor that supports microplastics entering the digestive tract is thought to be wrong in identifying prey, and this is microplastic similar to plankton, a natural fish food (Setala et al, 2014).…”
Section: Microplastics In Fishmentioning
confidence: 96%
“…The graph of the Abundance of microplastics in fish is presented in Figure 4. A study conducted by (Septiana et al, 2021) showed that microplastic content was also found in Channa striata species in Samarinda City (Sandra and Radityaningrum, 2021), showing the Abundance of microplastics in Oreochromis niloticus species in brackish waters of 1.47-7 particles/individual, and (Hasibuan et al, 2021) showed an abundance of microplastic 4.06-18.46 particles/individual in the Oreochromis mossambicus species. The main factor that supports microplastics entering the digestive tract is thought to be wrong in identifying prey, and this is microplastic similar to plankton, a natural fish food (Setala et al, 2014).…”
Section: Microplastics In Fishmentioning
confidence: 96%
“…The location of seawater sample collection near coastal residential areas allows for the frequent occurrence of fragment-type microplastics. This is due to the habit of residents disposing of waste into rivers, which then flows into the sea and breaks down into small pieces, forming fragments (Sandra and Radityaningrum, 2021).…”
Section: Abundance Of Microplastics In Sea Watermentioning
confidence: 99%
“…Selain itu,fiber juga berasal dari limbah kegiatan pecucian atau laundry baik dari industry massal atau industry rumah yang dibuang secara lagsung ke badan perairan dapat menghasilkan mikroplastik jenis fiber (Sandra & Radityaningrum, 2021). kelimpahan jenis mikroplastik yang terendah yaitu jenis fragmen, Tabel 2.…”
Section: Fragmentunclassified
“…Aktifitas perikanan seperti keramba jaring apung di sekitar sungai, serta kegiatan menangkap ikan menggunakan jarring dan pancing merupakan sumber mikroplastik jenis fiber karena jarring ikan terbuat dari plastic (Azizah dkk., 2020). Mikroplastik jenis fiber diketahui banyak mendominasi pada berbagai jenis penelitian (Ayuningtyas, 2019;Sandra & Radityaningrum, 2021). Banyaknya jenis fiber yang ditemukan karena pada saat pengambilan sampel ikan dan udang lokasinya berdekatan dengan rumah warga dimana limbah domestiknya dibuang ke sungai secara langsung.…”
Section: Spesiesunclassified